Airport capacity management: towards a slot allocation modelling approach compliant with IATA rules - Ribeiro, Nuno Antunes (2019)
Tese de Doutoramento em Sistemas de Transporte, apresentada ao Departamento de Engenharia Civil da Faculdade de Ciências e Tecnologia da Universidade de Coimbra